2009
DOI: 10.1063/1.3207827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uniaxial stress on ferroelectric behavior of (Bi1/2Na1/2)TiO3-based lead-free piezoelectric ceramics

Abstract: Prior studies have shown that a field-induced ferroelectricity in ceramics with general chemical formula (1−x−y)(Bi1/2Na1/2)TiO3-xBaTiO3-y(K0.5Na0.5)NbO3 and a very low remanent strain can produce very large piezoelectric strains. Here we show that both the longitudinal and transverse strains gradually change with applied electric fields even during the transition from the nonferroelectric to the ferroelectric state, in contrast to known Pb-containing antiferroelectrics. Hence, the volume change and, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 33 publications
11
65
0
Order By: Relevance
“…11 Such studies are vital for their implementation into devices. The following study presents macroscopic ferroelastic hysteresis curves for polycrystalline BNT-6BT at various temperatures from 25 to 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…11 Such studies are vital for their implementation into devices. The following study presents macroscopic ferroelastic hysteresis curves for polycrystalline BNT-6BT at various temperatures from 25 to 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy takes advantage of the fact that a poled FE ceramic contracts in volume when electric fields with a reversed polarity are applied and reaches a minimum volume around the coercive field ÀE c [12,18]. Since the compressive stress-induced FE-to-AFE phase transition is triggered by a critical volume contraction in FE oxides [16,17], it is conceived that the electric field-induced FE-to-AFE phase transition may also be realized and mediated by the volume contraction at ÀE c if the composition of the ceramic is properly tuned.…”
mentioning
confidence: 99%
“…27,28,36 Tan et al reported that addition of KNN in increasing quantities was also responsible for reduced depolarization temperature and increasing non-ferroelectric characteristics of the original BNT-BT composition. 44 It was observed that 0.91(Bi 0.5 Na 0.5 )TiO 3 -0.07BaTiO 3 -0.02(K 0.5 Na 0.5 )NbO 3 possess largely pseudo-cubic structure in contrast to 0.94(Bi 0.5 Na 0.5 )TiO 3 -0.05BaTiO 3 -0.01(K 0.5 Na 0.5 )NbO 3 which was characterized by a rhombohedral R3c symmetry and displays largely ferroelectric behavior. 44 The significant change was observed for only 1 mol.% change in the amount of KNN.…”
Section: A Materialsmentioning
confidence: 99%
“…44 It was observed that 0.91(Bi 0.5 Na 0.5 )TiO 3 -0.07BaTiO 3 -0.02(K 0.5 Na 0.5 )NbO 3 possess largely pseudo-cubic structure in contrast to 0.94(Bi 0.5 Na 0.5 )TiO 3 -0.05BaTiO 3 -0.01(K 0.5 Na 0.5 )NbO 3 which was characterized by a rhombohedral R3c symmetry and displays largely ferroelectric behavior. 44 The significant change was observed for only 1 mol.% change in the amount of KNN. For the purpose of our study we have used 0.91(Bi 0.5 Na 0.5 )TiO 3 -0.07BaTiO 3 -0.02(K 0.5 Na 0.5 )NbO 3 (BNT-BT-KNN) composition as it displays largely non-ferroelectric characteristics accompanied by large recoverable strains.…”
Section: A Materialsmentioning
confidence: 99%